2006
DOI: 10.1111/j.1365-2982.2006.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient‐dependent enhancement of rectal sensitivity in irritable bowel syndrome (IBS)

Abstract: Food-related gastrointestinal symptoms are common in irritable bowel syndrome (IBS), but the mechanisms behind this are unclear. Enhanced colorectal sensitivity after duodenal lipid administration in IBS patients has been demonstrated. However, the effects of a regular meal on colorectal sensitivity in these patients and the importance of the composition of the meal are not known. On two separate days, 10 IBS patients and 11 controls randomly received a liquid meal (800 kcal), containing 60% calories from fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 52 publications
3
43
2
Order By: Relevance
“…Accordingly, a number of studies assessed the effect of these triggers on visceral hypersensitivity in IBS patients. In general, these data showed that nutrient intake increased visceral hypersensitivity [32,34,35] and stress enhanced rectal sensitivity to a larger extent in IBS patients than in control subjects [36].…”
Section: Visceral Hypersensitivity and Ibsmentioning
confidence: 94%
See 1 more Smart Citation
“…Accordingly, a number of studies assessed the effect of these triggers on visceral hypersensitivity in IBS patients. In general, these data showed that nutrient intake increased visceral hypersensitivity [32,34,35] and stress enhanced rectal sensitivity to a larger extent in IBS patients than in control subjects [36].…”
Section: Visceral Hypersensitivity and Ibsmentioning
confidence: 94%
“…Patients with IBS often relate the onset or aggravation of symptoms following physiologic or pathologic events/ factors, including certain foods (eg, spicy food, fatty meals, coffee) [32] or stress [33]. Accordingly, a number of studies assessed the effect of these triggers on visceral hypersensitivity in IBS patients.…”
Section: Visceral Hypersensitivity and Ibsmentioning
confidence: 99%
“…Each patient came to the laboratory at 7:30 after an overnight fast, received a tap water enema (750 mL) for rectal emptying and was then positioned in a left lateral decubitus position in a hospital bed. All subjects underwent a rectal barostat study with two distension sequences, one before and one 60 min after an 800 kcal, 560 mL liquid meal (60% fat, 20% carbohydrate, 20% protein; 100 mL cream, 85 mL water, 100 mL Nutridrink, 275 mL Fortimel (Nutricia Nordic AB, Stockholm, Sweden)) 27. The barostat device consisted of a polyethylene balloon attached to a double-lumen polyvinyl tube (Salem Sump Tube, 18F; Sherwood Medical, Tullamore, Ireland).…”
Section: Methodsmentioning
confidence: 99%
“…Variability in the prevalence of visceral hypersensitivity across IBS patients (reviewed in reference 102) suggests that level of rectal sensitivity is not a biological marker of IBS, as was previously claimed (112). A number of factors affect visceral perception: gender (113), predominance of bowel dysfunction (114,115), psychological factors (116,117), and specifics of the experimental study protocol, such as inclusion of data on stress (118,119) or food ingestion (120,121). Whereas levels of pain and bloating have high correlation values with measures of visceral hypersensitivity (122), perceptual thresholds and ratings have only moderate correlation values with IBS symptom severity or response to treatment (91).…”
Section: Approaches To Proof Of Concept For Novel Ibs Drugsmentioning
confidence: 99%